2014
DOI: 10.3329/bjar.v39i2.20434
|View full text |Cite
|
Sign up to set email alerts
|

Yield and yield attributes of rapeseed – mustard (Brassica) genotypes grown under late sown condition

Abstract: A field experiment was conducted at the Central Research Station of BARI, Gazipur for two consecutive years 2010-11 and 2011-12 with 30 varieties/ genotypes of rapeseed-mustard under three dates of sowing viz., 25 November, 5 December, and 15 December to determine changes in crop phenology, growth and yield of mustard genotypes under late sown condition when the crop faced high temperature. Days to flowering and maturity were different at different planting times. Date of sowing significantly influenced plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 6 publications
6
10
0
Order By: Relevance
“…Among the dates, the higher aborted siliqua was observed in delayed sowing than earlier two dates. The first date of sowing had 2.850 aborted siliqua which is at par with second date of sowing with 3.950 aborted siliqua whereas the delayed date had 8.125, which is also in agreement with the study of Alam et al, (2014). The higher abortion of siliqua in delayed date might be due to severe fall in temperature and depleted soil residual moisture which hampered the fertilization process and nutritional translocation.…”
Section: Aborted Siliquasupporting
confidence: 87%
“…Among the dates, the higher aborted siliqua was observed in delayed sowing than earlier two dates. The first date of sowing had 2.850 aborted siliqua which is at par with second date of sowing with 3.950 aborted siliqua whereas the delayed date had 8.125, which is also in agreement with the study of Alam et al, (2014). The higher abortion of siliqua in delayed date might be due to severe fall in temperature and depleted soil residual moisture which hampered the fertilization process and nutritional translocation.…”
Section: Aborted Siliquasupporting
confidence: 87%
“…The maximum number of siliqua/plant was produced by the variety Improved Tori (120.27) and it was statistically similar with BARI sarisha-8, BARI sarisha-9, BARI sarisha-14 and BARI sarisha-15. Similar results were observed by Mondal et al [15] and Alam [12]. They were found maximum number of siliqua/plant (136) in the variety J-5004 which was identical with the variety Improved tori.…”
Section: Yield and Yield Attributes Of Rapeseed Mustardsupporting
confidence: 80%
“…It was supported by BARI, 2010 and produced 105.8 cm and 113.6 cm tallest plant in BARI Sarisha-8 and BARI Sarisha-15 respectively. Whereas, BARI Sharisa-14 produced the shortest plant (83.6 cm) which was supported by Ali et al [10], Bhuiyan [11] and Alam [12], Sana et al [13] reported that, the final plant height reflected the growth behavior of a crop.…”
Section: Growth Characteristics Of Different Rapeseed-mustardsupporting
confidence: 54%
“…Late sown Indian mustard is exposed to high temperature coupled with high evaporative demand of the atmosphere during the reproductive phase (ripening and grain filling) which consequently results in forced maturity and ultimately low productivity. High temperature in Brassica caused flower abortion with appreciable loss in seed yield [6]. Temperature can't be manipulated easily under field conditions but by modifying fertilizer doses and crop geometry of late sown Indian mustard, soil moisture loss may be adjusted to meet out the evaporative demand of the atmosphere during reproductive phase.…”
Section: Introductionmentioning
confidence: 99%